Futurology of Iran's Mining Industries with a Focus on Circular Economy - Ghanavati, Ebrahim; Maleki, Mohammad Hasan; Pourfakharan , Mohammad Reza; Safa, Mozhgan (Management Strategies and Engineering Sciences, 2024)
In today's world, the application of circular economy policies and programs plays a significant role in guiding the mining industries toward sustainable development. However, efforts to achieve sustainable development in Iran's mining industries have not been sufficiently serious. This study aims to explore the future of Iran's mining industries with a focus on the circular economy. Methodologically, this research employs a mixed-method approach and is exploratory in purpose. The study uses fuzzy Delphi, CoCoSo, and focus group interviews to assess the drivers and develop scenarios. In the first step, 33 drivers were identified through a literature review and interviews with experts in the mining industries. The drivers were then screened using expert validation questionnaires and the fuzzy Delphi technique. Nine drivers were selected for the final assessment using the CoCoSo method. These final drivers were prioritized through preference questionnaires and the CoCoSo method. Finally, future scenarios for the mining industries, focusing on the circular economy, were developed based on two prioritized drivers and interviews with focus groups. Based on the CoCoSo method scores and expert opinions, the drivers of government and large financial institutions' support, such as banks for waste management and recycling projects, and energy pricing policies in the country were the most prioritized factors influencing the future of mining industries with a focus on the circular economy. Four scenarios were developed based on the two final drivers and interviews with focus groups. These scenarios included: Generous Supporter, Sustainable Mining Industries, Dark Era, and Future-Oriented Policymakers. Practical recommendations were developed based on the most important drivers and the optimal scenario (Sustainable Mining Industries). Key recommendations include prioritizing waste management and recycling projects for financing by banks, shifting from directive policy-making to market-based and competitive policy-making, and leveraging green startups in research and development projects in the mining industries.